PENGARUH DOSIS ARANG TEMPURUNG KELAPA DAN KEPADATAN YANG BERBEDA TERHADAP SINTASAN BENIH IKAN MAS (CYPRINUS CARPIO) PADA PENGANGKUTAN SISTEM TERTUTUP: The Effect Of Coconut Shell Charcoal Doses And Different Densities On The Survival Of Gold Fish (Cyprinus Carpio) Seeds In Closed System Transportation - Arman Satriadi; Aryani Rahmawati; I Nyoman Budi Satria; Indah Soraya (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2023)
This study aims to determine the effect of coconut shell charcoal doses and different densities on closed system transportation which can increase the survival rate of goldfish (Cyprinus carpio) seeds. The method used in this study is an experimental method and the design used is Completely Randomized Design (CRD). The number of treatments A was divided into 4 levels namely (A1, A2, A3, and A4). Treatment B was divided into 3 levels (B1, B2, and B3) to obtain 12 experimental combinations with 3 repetitions for each combination to obtain 36 experimental units. The results showed that the highest survival rate of Goldfish (Cyprinus carpio) occurred in Treatment A1B1 (without the addition of coconut shell charcoal), as many as 287 fish/liter of water with an average survival rate (S/R) of 94 .5% and the lowest was A4B2 (with the addition of 45gr of charcoal) of 202 fish/liter of water with an average survival rate (S/R) of 66%